Analysis Of Langkat Regency Tourism Communication Strategy In Increasing Tourist Visit Interest - Habibi, Ariansyah; Achiriah (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2025)
This study aims to analyze the tourism communication strategy implemented by the Langkat Regency Tourism Office in increasing tourist interest. Langkat Regency has great natural and cultural potential, but has not been fully optimized through an effective and adaptive communication strategy to global trends. This study uses a qualitative approach with an explanatory research type, through observation techniques, in-depth interviews, and documentation. The results of the study show that the communication strategies used include the use of social media, the involvement of micro-influencers, strengthening locality-based destination narratives, developing a community-based creative economy, and cross-actor collaboration. This strategy has been able to build a positive destination image and strengthen tourists' emotional involvement in Langkat, especially through a digital approach and experience-based promotion. However, the study also found challenges such as inadequate infrastructure, low quality of service, and lack of integration between online promotion and the reality of services in the field. Referring to the Marketing Mix 7P theory, Langkat's communication strategy has not fully touched all aspects of the marketing mix in a balanced manner. Therefore, a more integrated and sustainability-based strategic approach is needed to build an inclusive, adaptive, and long-term oriented tourism communication system. This study is expected to be a reference in designing effective tourism communication policies for areas with similar characteristics and challenges. Langkat Communication has not fully touched all aspects of the marketing mix in a balanced manner. Therefore, a more integrated and sustainability-based strategic approach is needed to build an inclusive tourism communication system.